Uji Efektivitas Antibakteri Ekstrak Daun Kaki Kuda (Centella Asiatica) Terhadap Pertumbuhan Bakteri Propionibacterium Acnes - Wardani, Dini; Asdinar, Asdinar; Fatimah, Fatimah; Arwie, Dzikra; Safaruddin, Safaruddin (Universitas Sumatera Barat, 2023)
Infection is a disease caused by bacteria. Acne is an infectious disease caused by the bacteria Propionibacterium acnes. Acne can be treated with topical treatments such as using Benzoyl peroxide, Retinoid acid, and antibiotics, but this has the side effect of causing drug resistance. To prevent the emergence of resistance to antibiotics, a formula is needed that can utilize herbal plants as the main ingredient. One example of a herbal plant that can be used is horse's foot leaves. This herbal contains active ingredients in the form of Flavonoids, Saponins, Tannins, Steroids and Triterpenoids which are thought to inhibit the growth of bacteria, especially Propionibacterium acnes. The aim of this research is to determine the antibacterial effectiveness of horse's foot leaf extract (Centella asiatica) against the growth of Propionibacterium acnes bacteria at concentrations of 20%, 40%, 60%, 80%, 100%. The method used is a quantitative method, namely laboratory experiments. Horse's foot leaf extract was obtained by maceration then distilled which was then varied into several concentration treatments, namely 20%, 40%, 60%, 80%, 100%, as well as a positive control in the form of Tetracycline and a negative control of distilled water. Which is continued by using the well method. The results research show that horse's foot leaf extract can inhibit the growth of Propionibacterium acnes bacteria with moderate to strong inhibitory power. With a 20% concentration with an average inhibition zone of 7.6 mm, a 40% concentration of 9.3 mm, a 60% concentration of 10.3 mm, an 80% concentration of 11.6 mm and a 100% concentration which has the largest inhibition zone, namely 12.6mm.